The Political Economy of Italy in the EMU: What Went Wrong? - Leila Simona Talani (Journal of Economics and Political Economy, 2014)
Although Italy was amongst the most enthusiastic founding members of the European Economic Community in 1957, the Italian capacity to respect the imperatives of European integration could not, and, still, cannot, be given for granted, as the recent sovereign debt crisis demonstrates. Apart from the many structural inconsistencies that persist not only in the economic, but also in the political and social organization of the country, also the public debate is sometimes characterised by a tendency to blame the process of Europeanisation for the less palatable decisions taken by the national institutions. This article addresses the sub-national, national and supranational dimensions of the process of Italian Europeanisation focusing in particular on the role of domestic socio-economic actors in influencing monetary policy decision making processes. The article is based on field research conducted by the author both in Italy and Brussels. The main object of this research effort was to analyse to what extent the outcomes of the process of European monetary integration have been influenced by domestic politics and by domestic economic interest groups in Italy with the final aim of assessing the impact of Italian entry into the EMU and especially its future within it. Thus, at the core of this research lies the following question: What is the role of domestic politics and domestic interest groups in monetary policy-making? The theoretical starting point of this interpretation of the process of European monetary integration is represented by an integrated domestic-foreign policy focusing on the role of economic interest groups in defining national exchange rate and monetary policy decisions. It is not here the place to discuss the different theories explaining the process of European integration and, more specifically, of the issue of European monetary integration. Here it will simply be underlined that, to explain foreign economic policy choices, policy outcomes need to be linked to domestic politics.
Keywords: F31; F45; F51; 330; EMU; Eurozone crisis; Italy